De parque a mosaico: ecologia de paisagem no processo de recategorização do parque estadual Jacupiranga (SP) - Ocimar José Baptista Bim; Julia Camara de Assis; Marcos Buhrer Campolim; Sueli Angelo Furlan (Confins)
This study analyzes the process of re-categorization of the State Park of Jacupiranga into a Mosaic of Protected Areas (MOJAC) in dialogue with conservation designs recommended by the fundamentals of Landscape Ecology. We identified the state of the structural landscape connectivity within the fully protected areas and sustainable use areas in the MOJAC. The land cover and land use map used was the Forest Inventory of São Paulo developed through photointerpretation of aerial imagery of years 2000 and 2001, at the scale of 1: 35,000. The landscape metrics calculated for grouped classes of land use and land cover include total area and percentage of each class and path number. The MOJAC conservation status and the identification of regions more vulnerable to fragmentation were analyzed. Map reclassification and calculation of metrics were made using ArcGIS software version 9.3. The proposed mosaic does not bring risks for the conservation design, because the conserved structure of landscape indicates potential connections for species flow. The landscape has not been fragmented and the MOJAC may guarantee the preservation of large fragments. The protected areas with sustainable use should encourage agroecology and restauration projects.